ISU HUKUM DAN ETIKA DALAM PRAKTIK ANASTESI DI INDONESIA - Setionegoro, Adi Sakti (MAGISTRA Law Review, 2024)
Anesthesia practice in Indonesia faces challenges related to the application of professional and ethical standards as well as legal issues that often arise. This research aims to examine the application of professional and ethical standards in current anaesthesia practice in Indonesia and identify legal problems that frequently occur and how to resolve them. This research uses normative legal research methods by analyzing primary and secondary legal materials. The research results show that even though there are guidelines and codes of ethics governing anaesthesia practice, its implementation in the field still faces obstacles such as lack of understanding of health workers, excessive workload, lack of support from hospital management, and suboptimal supervision and sanctions. Legal problems often arise including negligence in administering anaesthesia, lack of informed consent, violations of the professional code of ethics, and problems in the doctor-patient relationship. Efforts that have been made to overcome these problems include increasing education and training, improving standard operational procedures, strengthening monitoring and sanctioning mechanisms, developing non-litigation dispute resolution pathways, improving communication and doctor-patient relationships, as well as increasing support from hospital management. However, these efforts are still not fully optimal and require further evaluation and improvement. The importance of individual awareness of each anaesthetist to comply with professional and ethical standards as well as strengthening ethical education is also a key factor. Close collaboration between various related parties is needed to improve the quality of anaesthesia practice in Indonesia while still prioritizing patient safety and welfare.